THE CONCEPT OF KENOSIS IN THEOLOGICAL THOUGHT OF V. N. LOSSKY AND ARCHPRIEST SERGII BULGAKOV: A COMPARATIVE CRITICAL ANALYSIS - Eduard A. Sablon Leiva ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
It has been found that the discrepancies between V. N. Lossky's and archpriest Sergii Bulgakov's views on kenosis are explained by the fact that these thinkers built their teachings on different methodological foundations, using different sources and tools. For Lossky, kenosis was temporal in nature and was limited to the christological dimension, while for Bulgakov kenosis meant an eternal intrathroic metaphysical reality that manifested itself much earlier and on a much larger scale. If Bulgakov insisted that the Incarnation was determined by ontological necessity (ontological altruism), then Lossky, by contrast, was of the opinion that it was caused by the need to solve the human problem of sin and became possible only due to the free act of the Divine will.